Energy-balancing Control Strategy for Modular Multilevel Converters Under Submodule Fault Conditions - Hu, Pengfei; Jiang, Daozhuo; Zhou, Yuebin; Liang, Yiqiao; Guo, Jie; Lin, Zhiyong (IEEE transactions on power electronics, 2014)
The modular multilevel converter (MMC) is a newly introduced switch-mode converter topology with the potential for high-voltage and high-power applications. This paper focuses on the design and control methods for fault-tolerant operation using redundant submodules (SMs), which is one of the most important features in the MMC topology. By comparing three design schemes of redundant SMs, the most economic and reliable scheme is identified. In addition, a mathematical model of the MMC with arms containing different numbers of SMs is developed. Based on the identified scheme and mathematical model, an energy-balancing control strategy is proposed to keep the MMC operating normally under SM fault conditions. Finally, time-domain simulations of a 61-level MMC system are performed, using the PSCAD/EMTDC software, while experiments are carried out on a 41-level MMC prototype. The simulation and experimental results validate the design scheme, mathematical model, and proposed energy-balancing control strategy.